Penggunaan game edukasi matematika dalam meningkatkan minat belajar siswa - Azzahro, Fatima (Maliki Interdisciplinary Journal, 2024)
Mathematics education is an important aspect in developing students’ critical and analytical thinking skills worldwide. However, low interest in learning mathematics often becomes a challenge in the education process, resulting in unsatisfactory academic achievements. Educational games in mathematics learning are recommended as a strategy to enhance students’ motivation and interest in learning. Educational math games increase students’ interest in learning compared to conventional methods. Educational games provide an interactive and enjoyable learning environment, which helps reduce anxiety about mathematics and increases students’ engagement in the learning process.